End-of-life pathology in UM-HET3 mice treated with 16 α‑hydroxyestradiol or late‑start canagliflozin - Jessica M. Snyder; David E. Harrison; Ron Korstanje; Brett Ginsburg; Peter C. Reifsnyder; James Nelson; Scott Leiser; Catherine Kaczorowski; Denise M. Imai; Adam B. Salmon; Randy Strong; Warren Ladiges; et al. (GeroScience, 2025)
Canagliflozin (Cana) started at 16 months of age and 16-hydroxy-estradiol (OH_Est) started at 12 months each led to significant increases in lifespan in male UM-HET3 mice but significant decreases in female lifespan. To seek insights into the basis for these sex-specific effects, we performed end-of-life histopathological analyses of control and treated mice for all three interventions testing program sites. There were no significant drug-induced alterations in inferred cause of death, although statistical power was low for such comparisons. Tabulation of incidental lesions (i.e., combining lethal and non-lethal lesions) revealed a complex set of significant and near-significant changes caused by each of the two agents, in some cases absent, or even opposite in direction, in one of the two sexes. The analysis did not, however, reveal a clear pattern that would explain the selective sex-specific effects of either agent on lifespan. It is plausible that the female-specific harm induced by each of these agents could reflect harmful or toxic effects that are not easily detectable by histopathological examination.